The SWOCC book of brand management models - SWOC (Amsterdam : SWOCC, 2008)
While the orignis of brands go back several centuries, theory on the subject only began to develop around 1990. Brands are very complex phenomena and lend themselves to a wide variety of approaches. This has resulted in a motley collection of theories, models and research methodologies and instruments that make it increasingly difficult to find one's way, especially for people with limited time for reading and contemplation. As a practical guide, Giep Franzen has composed an up-to-date overview of the most important models available for brand management. They are arranged in hierarchical order from corporate strategy models, via branding models, brand strategy models and advertising models, down to models for determining brand equity and financial brand value.the book is intended as a reference work for brand strategists. Whatever the problem area they are involved with, they will find a compact overview of current brand thinking here. In this revised version some of the models are reexamined and updated by their creators. Also, six new models are added.
Keywords: Marketing; Merken